(untitled) (Eurasian Journal of History, Geography and Economics, 2022)
In this article the author considers the transformation process as one of the temporary conditions for the development of economic systems that can replace sustainable development. One of the most important tasks of state economic policy is to balance the cyclical fluctuations of the development of economic systems. The actual and expected revenues of the main taxes of the budget of the Republic of Uzbekistan in 2022 were also analyzed. The main objectives of Uzbekistan’s medium-term fiscal policy will be considered. The article, focuses on the role of fiscal policy in addressing strategic issues of economic development. At the same time, the methods of logical and systematic analysis of tax risk in the context of digitalization of the economy, the views of foreign and domestic scholars are studied